2008
DOI: 10.1097/bcr.0b013e31818b9e5c
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Perioperative Antibiotic Prophylaxis May Improve Skin Autograft Survival in Patients With Acute Burns

Abstract: Skin autograft is the most important definitive treatment for acute-deep burns. Wound infection is the most important cause of autograft loss. Prior clinical studies have not shown any significant difference in the autograft survival rate and the use of perioperative systemic antibiotics. Their study assesses the potential benefit of systemic antibiotics in this setting, especially when topical antibiotics or artificial skin products are not readily available. The authors designed a prospective, randomized stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
0
18
0
2
Order By: Relevance
“…20,21 En el estudio llevado a cabo por Ergün y cols., 22 no se demostró que la profilaxis antibiótica sistémica fuera eficaz para prevenir la infección. Por el contrario, se relacionó con mayores tasas de infección, lo que coincide con lo observado en esta serie.…”
Section: Discussionunclassified
“…20,21 En el estudio llevado a cabo por Ergün y cols., 22 no se demostró que la profilaxis antibiótica sistémica fuera eficaz para prevenir la infección. Por el contrario, se relacionó con mayores tasas de infección, lo que coincide con lo observado en esta serie.…”
Section: Discussionunclassified
“…46 Antibiotic administration has been found to reduce the incidence of this transient bacteremia but not to affect outcomes. 47 A recently published study by Ramos et al 48 found that the use of systemic antibiotics administered perioperatively to patients undergoing grafting of deep burns was associated with improved autograft survival. However, the study had several limitations, including a small sample size, and more extensive follow-up studies will be required.…”
Section: Systemic Perioperative Antibiotic Prophylaxismentioning
confidence: 98%
“…However, there is some inconclusive evidence that in skin grafts systemic perioperative antibiotic prophylaxis contributes to the autograft survival [19]. Ramos et al found a rate of autograft survival for the group of patients with burns using two days of perioperative antibiotic prophylaxis of 97% versus 87% in the group without prophylaxis [20]. In patients with arterial and venous ulcers no differences in graft survival was observed with perioperative use of antibiotics [21].…”
Section: Discussionmentioning
confidence: 99%